The role of volunteer probation officers in Japan - Recent challenges and responses - Akashi, Fumiko (International journal of law, crime and justice, 2018)
The United Nations Standard Minimum Rules for Non-Custodial Measures (the Tokyo Rules) emphasize the importance of community acceptance of, and participation in, successful reintegration of offenders into society. One of the practices that fosters community involvement in offender treatment is the Volunteer Probation Officer (VPO) system. VPOs are community volunteers who are appointed as part-time government officials to support the work of professional probation officers. VPOs support the work of professional probation officers by supervising and assisting offenders in the communities in which they live. VPOs are key individuals who facilitate the rehabilitation of offenders as well as the acceptance of the offender by the community. However, in line with social and cultural changes, the Japanese VPO system is facing several challenges such as weaker bonds of the community and decreasing number of VPOs. In response, the Rehabilitation Bureau of the Ministry of Justice has implemented a number of measures, including the establishment of Offender Rehabilitation Support Centers and the creation of a new compensation scheme for property damage or injury suffered by VPOs or their family members. In many countries, VPOs and other volunteers play an important role in helping offenders reintegrate into the community. Comparing and learning from the approaches of other countries are important steps to enhance the effectiveness of probation through volunteers' activities.